Analysis of Second-Order HPF and LPF Circuit Simulations as Digital Signal Amplification Filters - Siregar, Pascal; Budi Setiawan, Florentius; Kariman, Paskal; Heru Pratomo, Leonardus; Riyadi, Slamet (Emitor: Jurnal Teknik Elektro, 2024)
The writing of this paper focuses on describing and relating simple modeling and analysis to the simulation of High-PassFilter (HPF) and Lowpass filter (LPF) designs using Op-Amp, which previously used an analog system and then converted into a digital system using input and output digital gain processing frequency which aims to strengthen the sinusoidal signal contained in the HPF and LPF systems. Filter is defined as an electrical network that is designed to pass alternating current that is increased at a predetermined frequency and blocks all alternating current that is increased at a predetermined frequency. Frequency also has types, namely analog, digital, active and passive. Analog filters are used for analog signals, digital are used for signals using digital techniques, passive filters such as resistors, capacitors, inductors, and active such as transistors or op-amps. In general, the understanding of HPF is that it passes high frequencies at the cut-off frequency and dampens low frequencies. Furthermore, LPF also has different characteristics, namely, passing low frequencies and dampening high frequencies. Currently related to digital signal processing, it can be said to be a method of manipulating, analyzing and interpreting signals, which is used to process the removal of noise or interference on several unwanted components of the signal. By knowing these characteristics, what the author did was carry out a simulation aimed at helping to obtain optimal frequency output.